Forbuddet mod Loyal to Familia - Kim Møller (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract On 1 September 2021, the Danish Supreme Court banned the gang Loyal to Familia (LTF) because it had an illegal aim and was therefore classified as an illegal association. This sentence marks a new understanding of the material limits to the constitutional freedom of association. It was the third ban of a Danish association, and the first ban of an association that did not have the aim of overthrowing democracy.